TEAD4 regulates trophectoderm differentiation upstream of CDX2 in a GATA3-independent manner in the human preimplantation embryo. Issue 8 (14th June 2022) - Stamatiadis, P; Cosemans, G; Boel, A; Menten, B; De Sutter, P; Stoop, D; Chuva de Sousa Lopes, S M; Lluis, F; Coucke, P; Heindryckx, B
Abstract: STUDY QUESTION: What is the role of transcriptional-enhanced associate (TEA) domain family member 4 ( TEAD4 ) in trophectoderm (TE) differentiation during human embryo preimplantation development in comparison to mouse? SUMMARY ANSWER: TEAD4 regulates TE lineage differentiation in the human preimplantation embryo acting upstream of caudal-type homeobox protein 2 ( CDX2), but in contrast to the mouse in a GATA-binding protein 3 ( GATA3 )-independent manner. WHAT IS KNOWN ALREADY: Tead4 is one of the earliest transcription factors expressed during mouse embryo preimplantation development and is required for the expression of TE-associated genes. Functional knock-out studies in mouse, inactivating Tead4 by site-specific recombination, have shown that Tead4 -targeted embryos have compromised development and expression of the TE-specific Cdx2 and Gata3 is downregulated. Cdx2 and Gata3 act in parallel pathways downstream of Tead4 to induce successful TE differentiation. Downstream loss of Cdx2 expression, compromises TE differentiation and subsequent blastocoel formation and leads to the ectopic expression of inner cell mass (ICM) genes, including POU Class 5 homeobox 1 ( Pou5f1 ) and SRY-box transcription factor ( Sox2 ). Cdx2 is a more potent regulator of TE fate in mouse as loss of Cdx2 expression induces more severe phenotypes compared with loss of Gata3 expression. The role of TEAD4 and its downstream effectors during human preimplantation embryo development has not been investigated yet. STUDY DESIGN, SIZE, DURATION: The clustered regularly interspaced short palindromic repeats—clustered regularly interspaced short palindromic repeats (CRISPR)-associated genes (CRISPR-Cas9) system was first introduced in pronuclei (PN)-stage mouse zygotes aiming to identify a guide RNA (gRNA), yielding high editing efficiency and effective disruption of the Tead4 locus. Three guides were tested (gRNA1-3), each time targeting a distinct region of Exon 2 of Tead4 . The effects of targeting on developmental capacity were studied in Tead4 -targeted embryos (n = 164—summarized data from gRNA1-3) and were compared with two control groups; sham-injected embryos (n = 26) and non-injected media-control embryos (n = 51). The editing efficiency was determined by next-generation sequencing (NGS). In total, n = 55 (summarized data from gRNA1-3) targeted mouse embryos were analysed by NGS. Immunofluorescence analysis to confirm successful targeting by gRNA1 was performed in Tead4 -targeted embryos, and non-injected media-control embryos. The downregulation of secondary TE-associated markers Cdx2 and Gata3 was used as an indirect confirmation of successful Tead4 -targeting (previously shown to be expressed downstream of Tead4) . Additional groups of gRNA1 Tead4 -targeted (n = 45) and media control (n = 36) embryos were cultured for an extended period of 8.5 days, to further assess the developmental capacity of the Tead4 -targeted group to develop beyond implantation stages. Following the mouse investigation, human metaphase-II (MII) oocytes obtained by IVM were microinjected with gRNA-Cas9 during ICSI (n = 74) to target TEAD4 or used as media-control (n = 33). The editing efficiency was successfully assessed in n = 25 TEAD4 -targeted human embryos. Finally, immunofluorescence analysis for TEAD4, CDX2, GATA3 and the ICM marker SOX2 was performed in TEAD4 -targeted (n = 10) and non-injected media-control embryos (n = 29). PARTICIPANTS/MATERIALS, SETTING, METHODS: A ribonucleoprotein complex consisting of a gRNA-Cas9 mixture, designed to target Exon 2 of Tead4 / TEAD4, was microinjected in mouse PN stage zygotes or human IVM MII oocytes along with sperm. Generated embryos were cultured in vitro for 4 days in mouse or 6.5 days in human. In mouse, an additional group of Tead4 -targeted and media-control embryos was cultured in vitro for an extended period of 8.5 days. Embryonic development and morphology were assessed daily, during culture in vitro of mouse and human embryos and was followed by a detailed scoring at late blastocyst stage. Targeting efficiency following gRNA-Cas9 introduction was assessed via immunostaining and NGS analysis. MAIN RESULTS AND THE ROLE OF CHANCE: NGS analysis of the Tead4 -targeted locus revealed very high editing efficiencies for all three guides, with 100% of the mouse embryos (55 out of 55) carrying genetic modifications resulting from CRISPR-Cas9 genome editing. More specifically, 65.22% (15 out 23) of the PN zygotes microinjected with gRNA1-Cas9, which exhibited the highest efficiency, carried exclusively mutated alleles. The developmental capacity of targeted embryos was significantly reduced (data from gRNA1), as 44.17% of the embryos arrested at the morula stage (2.5 days post coitum), coincident with the initiation of TE lineage differentiation, compared with 8.51% in control and 12.50% in sham control groups. High-quality blastocyst formation rates (Grade 3) were 8.97% in the gRNA1-targeted group, compared with 87.23% in the media-control and 87.50% in the sham group. Immunofluorescence analysis in targeted embryos confirmed downregulation of Tead4, Cdx2, and Gata3 expression, which resulted from successful targeting of the Tead4 locus. Tead4 -targeted mouse embryos stained positive for the ICM markers Pou5f1 and Sox2, indicating that expression of ICM lineage markers is not affected. Tead4 -targeted embryos were able to cavitate and form a blastocoel without being able to hatch. Extended embryo culture following zona pellucida removal, revealed that the targeted embryos can attach and form egg-cylinder-like structures in the absence of trophoblast giant cells. In human embryos, Exon 2 of TEAD4 was successfully targeted by CRISPR-Cas9 (n = 74). In total, 25 embryos from various developmental stages were analysed by NGS and 96.00% (24 out of 25) of the embryos carried genetic modifications because of gRNA-Cas9 editing. In the subgroup of the 24 edited embryos, 17 (70.83%) carried only mutant alleles and 11 out of these 17 (64.70%) carried exclusively frameshift mutations. Six out of 11 embryos reached the blastocyst stage. In contrast to mice, human-targeted embryos formed blastocysts at a rate (25.00%) that did not differ significantly from the control group (23.81%). However, blastocyst morphology and TE quality were significantly compromised following TEAD4 -targeting, showing grade C TE scores, with TE containing very few cells. Immunofluorescence analysis of TEAD4 -targeted embryos (n = 10) confirmed successful editing by the complete absence of TEAD4 and its downstream TE marker CDX2, but the embryos generated retained expression of GATA3, which is in contrast to what we have observed and has previously been reported in mouse. In this regard, our results indicate that GATA3 acts in parallel with TEAD4/CDX2 towards TE differentiation in human. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: CRISPR-Cas9 germline genome editing, in some cases, induces mosaic genotypes. These genotypes are a result of inefficient and delayed editing, and complicate the phenotypic analysis and developmental assessment of the injected embryos. We cannot exclude the possibility that the observed differences between mouse and human are the result of variable effects triggered by the culture conditions, which were however similar for both mouse and human embryos in this study. Furthermore, this study utilized human oocytes obtained by IVM, which may not fully recapitulate the developmental behaviour of in vivo matured oocytes. WIDER IMPLICATIONS OF THE FINDINGS: Elucidation of the evolutionary conservation of molecular mechanisms that regulate the differentiation and formation of the trophoblast lineage can give us fundamental insights into early implantation failure, which accounts for ∼15% of human conceptions. STUDY FUNDING/COMPETING INTEREST(S): The research was funded by the FWO-Vlaanderen (Flemish fund for scientific research, Grant no. G051516N), and Hercules funding (FWO.HMZ.2016.00.02.01) and Ghent University (BOF.BAS.2018.0018.01). G.C. is supported by FWO-Vlaanderen (Flemish fund for scientific research, Grant no. 11L8822N). A.B. is supported by FWO-Vlaanderen (Flemish fund for scientific research, Grant no. 1298722 N). We further thank Ferring Pharmaceuticals (Aalst, Belgium) for their unrestricted educational grant. The authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A.